Analisis dan Perancangan Pendeteksian Kesamaan Dokumen Teks Menggunakan Metode Latent Semantic Analysis - Erlan Darmawan; Rika Septian (NUANSA INFORMATIKA, 2014)
Plagiarism is often called coppying or making bouquets, opinions , and so forth from others and make it as his own essays and opinion ( KBBI , 1997: 775 ) . To detect whether a document is plagiarism or not, we need a document similarity detection system. This system is done in computerized text, and it used to detect similarities Latent Semantic Analisys method Â calculating the TF - IDF of each term in each document. In this paper, a system built using the Java programming language with Netbeans IDE. It can be concluded documents with similarity levels above 70 % can be said to be plagiarism.Keywords : Plagiarism , Similarity , LSA , TF - IDF